2008
DOI: 10.1063/1.2992135
|View full text |Cite
|
Sign up to set email alerts
|

Mode conversion of nonaxisymmetric modes in strongly nonuniform helicon-sustained plasma

Abstract: The oblique wave propagation in helicon-sustained plasma accounting for the effect of the radial electron density gradient is investigated. It is shown that the conditions for the conversion of electrostatic and electromagnetic modes may change drastically in strongly nonuniform helicon plasma due to modification of the wave dispersion branches. Furthermore, the densities at which mode conversion occurs can be considerably lower if the density gradient is steep enough. This result contrasts with the common mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Nevertheless, theoretical investigations carried out very recently show that the conversion zone in strongly nonuniform plasma can shift to much lower densities. 18 Indeed, the density gradient associated with the peak near the axis occurring at high power is steep enough to fulfill the new conversion condition given in Ref. 18, whereas this does not hold for the relatively smooth profile at small power.…”
Section: -7mentioning
confidence: 95%
See 1 more Smart Citation
“…Nevertheless, theoretical investigations carried out very recently show that the conversion zone in strongly nonuniform plasma can shift to much lower densities. 18 Indeed, the density gradient associated with the peak near the axis occurring at high power is steep enough to fulfill the new conversion condition given in Ref. 18, whereas this does not hold for the relatively smooth profile at small power.…”
Section: -7mentioning
confidence: 95%
“…18 Indeed, the density gradient associated with the peak near the axis occurring at high power is steep enough to fulfill the new conversion condition given in Ref. 18, whereas this does not hold for the relatively smooth profile at small power. Further theoretical work on helicon absorption in nonuniform plasma has been done by Breizman and Arefiev 19 who predicted radially localized helicon modes which may lead to efficient rf absorption.…”
Section: -7mentioning
confidence: 95%
“…When the collision is absent, dispersion curves of HÀ and TGþ merge at x ¼ x up , corresponding to the MCS where the discriminant in (10) is zero, and the HÀ mode converts to the TGþ as the reflected wave. When a finite collision is added, the dispersion curves are separated because the discriminant in (10) includes the imaginary part and cannot be zero (the same discussion holds for the case with including the effect of strong density gradient 10 in (10)). The separation is increased as =x is increased, reducing efficiency of the mode conversion between the HÀ and TGþ waves.…”
Section: A Dispersion Relationmentioning
confidence: 98%
“…[14][15][16][17] Even in laboratory plasmas with moderate density gradient, the inhomogeneity may be strong in a) Electronic mail: michael.kraemer@ruhr-uni-bochum.de 1070-664X/2014/21(1)/013508/9/$30.00 V C 2014 AIP Publishing LLC 21, 013508-1 the sense outlined in Sec. II.…”
Section: Introductionmentioning
confidence: 98%
“…In Ref. 15, we investigated conversion of helicon modes into electrostatic modes and demonstrated that mode conversion may strongly be affected by the plasma density gradient as well. We showed for m > 0 modes that the plasma density, at which mode conversion occurs, can be much lower than in weakly inhomogeneous plasma because helicon modes and ES modes being involved in mode conversion may drastically alter their dispersion behavior in the presence of a strong radial density gradient.…”
Section: Introductionmentioning
confidence: 99%